CD105 (Endoglin) exerts prognostic effects via its role in the microvascular niche of paediatric high grade glioma - Smith, Stuart J.; Tilly, Hanna; Ward, Jennifer H.; Macarthur, Donald C.; Lowe, James; Coyle, Beth; Grundy, Richard G. (Springer Verlag, 2012)
Paediatric high grade glioma (pHGG) (World Health Organisation astrocytoma grades III and IV) remains poor prognosis tumours, with a median survival of only 15 months following diagnosis. Current investigation of anti-angiogenic strategies has focused on adult glioblastoma multiforme (GBM) with phase III trials targeting vascular endothelial growth factor continuing. In this study we investigated whether the degree of vascularity correlated with prognosis in a large cohort of pHGG (n = 150) and whether different vessel markers carried different prognostic value. We found that CD105 (endoglin) had a strongly significant association with poor prognosis on multivariate analysis (p = <0.001). Supervised hierarchical clustering of genome wide gene expression data identified 13 genes associated with differential degrees of vascularity in the cohort. The novel angiogenesis-associated genes identified in this analysis (including MIPOL-1 and ENPP5) were validated by realtime polymerase chain reaction. We also demonstrate that CD105 positive blood vessels associate with CD133 positive tumour cells and that a proportion of CD105 positive vessel cells demonstrates co-positivity for CD133, suggesting that the recently described phenomenon of vasculogenic mimicry occurs in pHGG. Together, the data suggest that targeting angiogenesis, and in particular CD105, is a valid therapeutic strategy for pHGG.